2020
DOI: 10.1186/s12874-020-01153-1
|View full text |Cite
|
Sign up to set email alerts
|

Survival prediction models since liver transplantation - comparisons between Cox models and machine learning techniques

Abstract: Background Predicting survival of recipients after liver transplantation is regarded as one of the most important challenges in contemporary medicine. Hence, improving on current prediction models is of great interest.Nowadays, there is a strong discussion in the medical field about machine learning (ML) and whether it has greater potential than traditional regression models when dealing with complex data. Criticism to ML is related to unsuitable performance measures and lack of interpretabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 49 publications
(58 reference statements)
2
35
0
Order By: Relevance
“…7 demonstrate that the proposed deep learning method can achieve much superior performance over the benchmark CPH model and the RSF model. A previous study 43 demonstrated that the CPH model normally has limited performance owing to the proportional hazard assumption, and the RSF model is more suitable for complicated applications as it can build a nonlinear relationship between the variables and outcomes. However, RSF is a nondifferentiable model and is widely recognized in processing discrete variables (e.g., the symptoms and comorbidities investigated in this study).…”
Section: Discussionmentioning
confidence: 99%
“…7 demonstrate that the proposed deep learning method can achieve much superior performance over the benchmark CPH model and the RSF model. A previous study 43 demonstrated that the CPH model normally has limited performance owing to the proportional hazard assumption, and the RSF model is more suitable for complicated applications as it can build a nonlinear relationship between the variables and outcomes. However, RSF is a nondifferentiable model and is widely recognized in processing discrete variables (e.g., the symptoms and comorbidities investigated in this study).…”
Section: Discussionmentioning
confidence: 99%
“…At its most basic level, machine learning may not offer improvement over currently existing statistical methods. Kantidakis et al (22) demonstrated only a marginal improvement in IBS and C-index for predicting survival in kidney transplants with their advanced computational models; Miller et al (31) demonstrated no added benefit of their models to current risk indices.…”
Section: Predicting Clinical Outcomes After Solid Organ Transplantation With Machine Learningmentioning
confidence: 99%
“…( 30 ) generated a tree of predictors for cardiac transplant and Kantidakis et al. ( 22 ) demonstrated improved predictability using random forest survival analysis in kidney transplant compared with Cox models. Bertsimas et al.…”
Section: Predicting Clinical Outcomes After Solid Organ Transplantation With Machine Learningmentioning
confidence: 99%
See 2 more Smart Citations